Psychosocial interventions and needs among individuals and families with Li‐Fraumeni syndrome: A scoping review. Issue 2 (23rd August 2021) - Barnett, Marie; Breen, Kelsey E.; Kennedy, Jennifer A.; Hernandez, Marisol; Matsoukas, Konstantina; MacGregor, Meredith
Abstract: Li‐Fraumeni syndrome (LFS), a rare cancer predisposition syndrome caused by germline mutations in the TP53 gene, is associated with significant lifetime risk of developing cancer and warrants extensive and long‐term surveillance. There are psychosocial impacts on individuals and families living with this condition, from the initial diagnosis throughout multiple stages across the lifespan, but these impacts have not been systematically reviewed and organized. The objective of this scoping review was to synthesize and characterize the literature on psychosocial screening and outcomes, educational needs, support services, and available interventions for patients and families with LFS. A systematic search of six databases was most recently conducted in August 2020: (PubMed/MEDLINE (NLM), EMBASE (Elsevier), Cochrane Library (Wiley), CINAHL (EBSCO), PsycINFO (OVID), and Web of Science (Clarivate Analytics). A total of 15 757 titles were screened, and 24 articles included. Several important themes were identified across studies: factors associated with TP53 genetic testing, LFS surveillance, psychological outcomes, and communication. Findings related to these themes were organized into age‐specific categories (age agnostic/across the lifespan, childhood, adolescence and young adulthood, and adulthood). Abstract :